(untitled) (American Journal of Technology and Applied Sciences, 2025)
Digital twin technology has emerged as a transformative approach in engineering, manufacturing, and design, enabling real-time simulation, monitoring, and optimization of physical systems. Descriptive Geometry tools provide essential capabilities for constructing, visualizing, and analyzing geometric representations within digital twin frameworks. This study explores the integration of Descriptive Geometry in virtual prototyping processes, emphasizing 3D modeling, parametric design, and simulation of complex systems. Following the IMRaD structure, the research combines a comprehensive literature review, case studies of digital twin applications, and experimental implementation using advanced geometric tools. Results indicate that leveraging Descriptive Geometry enhances model accuracy, facilitates predictive analysis, and improves the fidelity of virtual prototypes. The discussion addresses methodological considerations, integration challenges, and potential improvements in design workflows. The conclusion underscores the pivotal role of Descriptive Geometry in realizing effective digital twin systems, enhancing design, operational efficiency, and decision-making.